Born entrepreneur? Adolescents' personality characteristics and self-employment in adulthood - Jutta Viinikainen; Guido Heineck; Petri Böckerman; Mirka Hintsanen; Olli Raitakari; Jaakko Pehkonen (Bamberg University, Bamberg Economic Research Group (BERG), 2016)
Is there an entrepreneurial personality and does it appear early in life? We provide a new answer on this question by using the so-called Type A behavior traits (Aggression, Leadership, Responsibility, and Eagerness-Energy), measured in childhood and adolescence, and examining their relationship to self-employment propensity in adulthood. Using data from the Young Finns Study linked to the Finnish Longitudinal Employer-Employee Data and the Longitudinal Population Census of Statistics, our results show that the early-life Leadership-dimension is significantly associated with a higher likelihood 1) of becoming self-employed later in life and 2) of being more successful as an entrepreneur, as approximated by sales. Our results also reinforce the prior evidence on the intergenerational transmission of entrepreneurship.
Keywords: L26; 330; Type A behavior; personality; self-employment; entrepreneurship; intergenerational transmission of entrepreneurship